Respuesta :

Answer:

[tex](x -y)^2 = -1[/tex]

Step-by-step explanation:

[tex](x - y)^2 = x^2 + y^2 - 2xy[/tex]

           [tex]= (x^2 + y^2 ) - 2(xy)\\\\=(9) - 2( 5)\\\\= 9 - 10 \\\\ = -1[/tex]

Solution:

The binomial expansion of (x - y)² is

(x - y)² = x² - 2xy + y²

Substitute the given values to the equation

(x - y)² = x² - 2xy + y²

(x - y)² = x² + y² - 2xy

(x - y)² = 9 - 2(5)

(x - y)² = 9 - 10

(x - y)² = -1

Therefore the value of (x - y)² is -1.

#ILoveMath

#ILoveYouShaina

ACCESS MORE